Supply chain management performance measurement in the development of Indonesian new capital city using SCOR method - Bambang Handoko; Angga Widyas Swara (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The current issue of the Indonesian people is that there is a discussion about the discourse of moving the new capital city.  The process of moving capital city requires a lot of qualified human and material resources, but whether we can see whether it is possible for the capital city to move in a very short time. Logistics and supply chains are two things that are not separated in the process of moving goods and services. Supply chain management in the construction of new capital city includes material, heavy equipment, human resource   services and suppliers. The objective of this research is to develop the framework of supply chain performance measurement using SCOR method. Through SCOR research, can be traced anywhere that needs to produce more in terms of human resources and materials needed in the future, then the government needs to build a framework of indicators that must be achieved and targeted.